Identification of Steroidogenic Components Derived From Gardenia jasminoides Ellis Potentially Useful for Treating Postmenopausal Syndrome - Wang, Xueyu; Wang, Guo-Cai; Rong, Jianhui; Wang, Shi Wei; Ng, Tzi Bun; Zhang, Yan Bo; Lee, Kai Fai; Zheng, Lin; Wong, Hei-Kiu; Yung, Ken Kin Lam; Sze, Stephen Cho Wing (Frontiers in Pharmacology, 2018)
Estrogen-stimulating principles have been demonstrated to relieve postmenopausal syndrome effectively. Gardenia jasminoides Ellis (GJE) is an herbal medicine possessing multiple pharmacological effects on human health with low toxicity. However, the therapeutic effects of GJE on the management of postmenopausal syndrome and its mechanism of action have not been fully identified. In this study, network pharmacology-based approaches were employed to examine steroidogenesis under the influence of GJE and in addition, the possibility of toxicity of GJE was ruled out and four probably active compounds were predicted. In parallel, a chromatographic fraction of GJE with estrogen-stimulating effect was identified and nine major compounds were isolated from this active fraction. Among the nine compounds, four of them were identified by network pharmacology, validating the use of network pharmacology to predict active compounds. Then the phenotypic approaches were utilized to verify that rutin, chlorogenic acid (CGA) and geniposidic acid (GA) exerted an estrogen-stimulating effect on ovarian granulosa cells. In addition, the results of target-based approaches indicated that rutin, CGA and GA could up-regulate the FSHR-aromatase pathway in ovarian granulosa cells. The estrogen-stimulating effects produced by the three compounds were partially rescued in the follicle-stimulating hormone receptor (FSHR)-attenuated ovarian granulosa cell model, indicating the involvement of FSHR in the estradiol-stimulating activity of the three compounds. The effects of the three compounds on estrogen biosynthesis- related gene expression level were further confirmed by Western blot assay. Importantly, the MTT results showed that exposure of breast cancer cells to the three compounds resulted in reduction of cell viability, demonstrating the cytotoxicity of the three compounds. Collectively, rutin, chlorogenic acid and geniposidic acid appear to play an important therapeutic role in GJE for the treatment of postmenopausal syndrome.